EFFICIENCY OF FISCAL POLICY - Hidoyatovna, Kamilova Mashkura; kizi, Hamdamova Zukhra Ulugbek (Antis Publisher, 2024)
Fiscal policy, a crucial tool in the hands of policymakers, aims to stabilize the economy by manipulating government expenditures and taxation. However, the efficiency of fiscal policy in achieving its objectives has been a subject of ongoing debate among economists. Using a combination of theoretical and empirical approaches, this research assesses the effectiveness of fiscal policy in responding to economic shocks, promoting sustainable growth, and reducing income inequality. The study also explores the role of fiscal policy in stabilizing the business cycle, managing public debt, and influencing inflation. The study concludes that fiscal policy can be an effective tool in stabilizing the economy and promoting growth, but its efficiency is highly dependent on the specific context in which it is implemented. The research contributes to the existing literature by providing insights into the optimal design and implementation of fiscal policy, highlighting the importance of careful consideration of the economic environment and the potential risks associated with fiscal policy interventions. The study's findings have significant implications for policymakers, emphasizing the need for a nuanced and evidence-based approach to fiscal policy decision-making. Conclusions, recommendations and proposal are presented in the article can be used in the implementation effective fiscal policies aimed at creating favorable institutional conditions for the implementation tax reform of the public sector..